Effect of Pressure on The Valency of Ytterbium in Ytterbium Monochalcogenides - Baral, Shiva Prasad; Adhikari, Shesh Kant; Adhikari, Dipak Raj (Amrit Research Journal, 2025)
When pressure is applied then properties of material change due to the alteration of of valency. Several effects of pressure on the characteristics of material have been investigated. This study was focused at finding the change in valency as a function of pressure of Ytterbium Monochalcogenides YbX (X=S, Se and T). The change in valency of Ytterbium in Ytterbium monochalcogenides as functions of pressure have been calculated by using the modified data. For calculating the change in valency of Yb, the modified experimental pressure-volume relationships of YbS, YbSe and YbTe have been reproduced by using the Birch–Murnaghan equation. The equivalent pressure-volume relationships of these materials for stable divalent Ytterbium have also been calculated using the same equation. The change in valency is calculated by a method, that assumes the variation between the calculated and experimental lattice constants at separately pressure value of the assumed material.